A hybrid anode schottky diode and its preparation method and application

CN117276354BActive Publication Date: 2026-10-09SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311207872.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-18
Publication Date
2026-10-09
Estimated Expiration
2043-09-18

AI Technical Summary

Technical Problem

然而,传统的AlGaN/GaN SBD器件无法兼具低开启电压和高反向击穿电压,器件的频率和效率还有待进一步提高

Benefits of technology

[0041] The beneficial effects of the present invention are: the hybrid anode Schottky diode of the present invention contains Schottky contact anodes of different depths, which, combined with the ohmic contact anode, can improve the reverse breakdown voltage of the device by adjusting the two-dimensional electron gas (2DEG) density of the channel layer, and can also improve the forward conduction voltage and on-resistance of the device, which is conducive to achieving simultaneous improvement of device frequency and efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117276354B_ABST
    Figure CN117276354B_ABST
Patent Text Reader

Abstract

The application discloses a mixed anode Schottky diode and a preparation method and application thereof. The composition of the mixed anode Schottky diode comprises a substrate, a GaN channel layer, an AlGaN barrier layer and a silicon nitride passivation layer which are sequentially arranged in layers, and further comprises an ohmic contact cathode, an ohmic contact anode, a first Schottky contact anode, a second Schottky contact anode and an anode field plate. The mixed anode Schottky diode contains Schottky contact anodes with different depths, which, in combination with the ohmic contact anode, can improve the reverse breakdown voltage of the device by adjusting the two-dimensional electron gas density of the channel layer, and can also improve the forward conduction voltage and conduction resistance of the device, thereby being beneficial to the synchronous improvement of the frequency and efficiency of the device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor device technology, specifically to a hybrid anode Schottky diode, its fabrication method, and its applications. Background Technology

[0002] Schottky diodes (SBDs) are high-current, low-power, low-voltage, and ultra-high-speed semiconductor power devices made with a noble metal anode (molybdenum, gold, silver, etc.) and an N-type semiconductor cathode. They utilize the rectification characteristics of the potential barrier formed at the interface between these two materials. AlGaN / GaN Schottky diodes are typical representatives of GaN-based SBD devices, possessing characteristics such as a large bandgap, high breakdown electric field strength, significant polarization effect, and high saturated electron drift velocity. They are well-suited for use as switching devices in rectifier circuits, switching voltage regulator circuits, inverters, power factor correction, and other electrical circuits, showing great market potential. However, traditional AlGaN / GaN SBD devices cannot simultaneously achieve both low turn-on voltage and high reverse breakdown voltage; further improvements in frequency and efficiency are needed.

[0003] Therefore, developing a Schottky diode with low turn-on voltage and high reverse breakdown voltage is of great significance. Summary of the Invention

[0004] The purpose of this invention is to provide a hybrid anode Schottky diode, its preparation method, and its application.

[0005] The technical solution adopted in this invention is:

[0006] A hybrid anode Schottky diode comprises a substrate, a GaN channel layer, an AlGaN barrier layer, and a silicon nitride passivation layer stacked sequentially, and further comprises an ohmic contact cathode, an ohmic contact anode, a first Schottky contact anode, a second Schottky contact anode, and an anode field plate. The ohmic contact cathode penetrates the silicon nitride passivation layer and is partially embedded in the AlGaN barrier layer to form an ohmic contact. The ohmic contact anode penetrates the silicon nitride passivation layer and is partially embedded in the AlGaN barrier layer to form an ohmic contact. The first Schottky contact anode penetrates the silicon nitride passivation layer and is partially embedded in the AlGaN barrier layer to form a Schottky contact. The second Schottky contact anode penetrates both the silicon nitride passivation layer and the AlGaN barrier layer and is partially embedded in the GaN channel layer to form a Schottky contact. The anode field plate penetrates the silicon nitride passivation layer and is in contact with the AlGaN barrier layer.

[0007] Preferably, the substrate is one of SiC substrate, Si substrate, sapphire substrate, and GaN single crystal substrate.

[0008] Preferably, the thickness of the GaN channel layer is 1 μm to 5 μm.

[0009] Preferably, the thickness of the AlGaN barrier layer is 5 nm to 17 nm.

[0010] Preferably, the thickness of the silicon nitride (Si3N4) passivation layer is 50nm to 100nm.

[0011] Preferably, the ohmic contact cathode is composed of at least one of Ti, Al, Ni, and Au.

[0012] More preferably, the ohmic contact cathode is composed of one of Ti-Al alloy and Ti-Al-Ni-Au alloy.

[0013] Preferably, the ohmic contact anode is composed of at least one of Ti, Al, Ni, and Au.

[0014] More preferably, the ohmic contact anode is composed of one of Ti-Al alloy and Ti-Al-Ni-Au alloy.

[0015] Preferably, the first Schottky contact anode is composed of at least one of Ni, W, Pt, Ti, and Au.

[0016] More preferably, the first Schottky contact anode is composed of one of Ni-Au alloy, W-Au alloy, and Pt-Au alloy.

[0017] Preferably, the second Schottky contact anode is composed of at least one of Ni, W, Pt, Ti, and Au.

[0018] More preferably, the second Schottky contact anode is composed of one of Ni-Au alloy, W-Au alloy, and Pt-Au alloy.

[0019] Preferably, the anode field plate is composed of at least one of Ni, W, Pt, Ti, and Au.

[0020] More preferably, the anode field plate is composed of one of Ni-Au alloy, W-Au alloy, and Pt-Au alloy.

[0021] Preferably, one or more ohmic contact cathodes are provided.

[0022] Preferably, the first Schottky contact anode is provided with one or more.

[0023] Preferably, the second Schottky contact anode is provided with one or more.

[0024] A method for fabricating a hybrid anode Schottky diode as described above includes the following steps:

[0025] 1) GaN channel layer and AlGaN barrier layer are epitaxially grown sequentially on the substrate surface by metal-organic chemical vapor deposition (MOCVD) or molecular beam epitaxy (MBE);

[0026] 2) A silicon nitride passivation layer is epitaxially grown on the surface of the AlGaN barrier layer by low-pressure chemical vapor deposition (LPCVD), plasma-enhanced chemical vapor deposition (PECVD), or atomic layer deposition (ALD).

[0027] 3) The epitaxial wafer obtained in step 2) is exposed by photolithography to expose the ohmic contact cathode and ohmic contact anode fabrication regions. The silicon nitride passivation layer in these two regions is completely removed by chemical etching. Then, part of the AlGaN barrier layer in these two regions is removed by inductively coupled plasma etching (ICP). Finally, metal evaporation, photoresist stripping and annealing are performed to form the ohmic contact cathode and ohmic contact anode electrodes.

[0028] 4) The first Schottky contact anode fabrication region is exposed by photolithography on the epitaxial wafer obtained in step 3). The silicon nitride passivation layer in this region is completely removed by chemical etching. Then, part of the AlGaN barrier layer in this region is removed by inductively coupled plasma etching. Finally, metal evaporation and photoresist stripping are performed to form the first Schottky contact anode.

[0029] 5) The epitaxial wafer obtained in step 4) is photolithographically exposed to expose the second Schottky contact anode fabrication region. Then, the silicon nitride passivation layer and AlGaN barrier layer in this region are completely removed by chemical etching. Then, part of the GaN channel layer in this region is removed by inductively coupled plasma etching. Then, metal evaporation and photoresist stripping are performed to form the second Schottky contact anode.

[0030] 6) The epitaxial wafer obtained in step 5) is photolithographically exposed to expose the anode field plate preparation area. Then, the silicon nitride passivation layer in this area is completely removed by chemical etching. Then, metal evaporation and photoresist stripping are performed to form the anode field plate, thus obtaining the hybrid anode Schottky diode.

[0031] Preferably, in step 1), the GaN channel layer is grown by metal-organic chemical vapor deposition at a growth temperature of 850℃~950℃.

[0032] Preferably, in step 1), an AlGaN barrier layer is grown by metal-organic chemical vapor deposition at a growth temperature of 750℃ to 850℃.

[0033] Preferably, in step 2), a silicon nitride passivation layer is grown by plasma-enhanced chemical vapor deposition at a growth temperature of 230°C to 320°C.

[0034] Preferably, the etching solution used in steps 3) to 6) is a buffered oxide etching solution, and the chemical etching time is 50s to 100s.

[0035] Preferably, the mass ratio of HF to NH4F in the buffer oxide etching solution is 1:5 to 7.

[0036] Preferably, the etching depth of the AlGaN barrier layer in step 3) is 2nm to 8nm.

[0037] Preferably, the annealing in step 3) is carried out in a nitrogen atmosphere at a temperature of 800℃~900℃ for a time of 20s~60s.

[0038] Preferably, the etching depth of the AlGaN barrier layer in step 4) is 3nm to 13nm.

[0039] Preferably, the etching depth of the GaN channel layer in step 5) is 2nm to 5nm.

[0040] An electronic product comprising the aforementioned hybrid anode Schottky diode.

[0041] The beneficial effects of the present invention are: the hybrid anode Schottky diode of the present invention contains Schottky contact anodes of different depths, which, combined with the ohmic contact anode, can improve the reverse breakdown voltage of the device by adjusting the two-dimensional electron gas (2DEG) density of the channel layer, and can also improve the forward conduction voltage and on-resistance of the device, which is conducive to achieving simultaneous improvement of device frequency and efficiency.

[0042] Specifically:

[0043] 1) The hybrid anode Schottky diode of the present invention adopts a composite deep hybrid anode structure, which can effectively control the two-dimensional electron gas distribution of the channel layer by the thickness of the barrier layer, improve the electric field and charge distribution between the anode and cathode under reverse bias, thereby improving the reverse breakdown voltage of the device;

[0044] 2) In the hybrid anode Schottky diode of the present invention, the second Schottky contact anode directly penetrates the AlGaN barrier layer and contacts the two-dimensional electron gas of the GaN channel layer, which can effectively reduce the junction capacitance of the device under forward bias.

[0045] 3) The hybrid anode Schottky diode of the present invention adopts a hybrid anode (ohmic contact anode) structure. This ohmic contact can effectively reduce the on-resistance of the device when the device is forward turned on, and at the same time reduce the turn-on voltage of the device. Attached Figure Description

[0046] Figure 1This is a schematic diagram of the hybrid anode Schottky diode of Example 1.

[0047] Figure 2 This is a schematic diagram of the hybrid anode Schottky diode in Example 2.

[0048] Figure 3 This is a schematic diagram of a Schottky diode for comparison.

[0049] Explanation of reference numerals in the attached figures: 10, substrate; 20, GaN channel layer; 30, AlGaN barrier layer; 40, silicon nitride passivation layer; 50, ohmic contact cathode; 60, ohmic contact anode; 70, first Schottky contact anode; 80, second Schottky contact anode; 90, anode field plate.

[0050] Figure 4 This is a comparison chart of the reverse leakage current and breakdown performance of the hybrid anode Schottky diode of Example 1 and the Schottky diode of the comparative example. Detailed Implementation

[0051] The present invention will be further explained and described below with reference to specific embodiments.

[0052] Example 1:

[0053] A hybrid anode Schottky diode (structural schematic shown) Figure 1 As shown, it comprises a substrate 10, a GaN channel layer 20, an AlGaN barrier layer 30, a silicon nitride passivation layer 40, an ohmic contact cathode 50, an ohmic contact anode 60, a first Schottky contact anode 70, a second Schottky contact anode 80, and an anode field plate 90; the substrate 10, GaN channel layer 20, AlGaN barrier layer 30, and silicon nitride passivation layer 40 are sequentially stacked; the ohmic contact cathode 50 penetrates the silicon nitride passivation layer 40 and is partially embedded in the AlGaN barrier layer 30 to form an ohmic contact with the AlGaN barrier layer 30; the ohmic contact anode 60 penetrates the silicon nitride passivation layer 40 and is partially embedded in the AlGaN barrier layer 30. The N-type barrier layer 30 forms an ohmic contact with the AlGaN barrier layer 30; the first Schottky contact anode 70 penetrates the silicon nitride passivation layer 40 and is partially embedded in the AlGaN barrier layer 30 to form a Schottky contact with the AlGaN barrier layer 30; the second Schottky contact anode 80 penetrates the silicon nitride passivation layer 40 and the AlGaN barrier layer 30 and is partially embedded in the GaN channel layer 20 to form a Schottky contact with the GaN channel layer 20; the ohmic contact anode 60, the first Schottky contact anode 70, and the second Schottky contact anode 80 are in contact with each other; the anode field plate 90 penetrates the silicon nitride passivation layer 40 and is in contact with the AlGaN barrier layer 30.

[0054] The fabrication method of the above-mentioned hybrid anode Schottky diode is as follows:

[0055] 1) A GaN channel layer with a thickness of 1 μm was epitaxially grown on the surface of a Si substrate by metal-organic chemical vapor deposition (MOCVD) at a growth temperature of 850℃, and then an AlGaN barrier layer with a thickness of 10 nm was epitaxially grown at a growth temperature of 800℃.

[0056] 2) A silicon nitride passivation layer with a thickness of 100 nm was epitaxially grown on the surface of the AlGaN barrier layer by plasma-enhanced chemical vapor deposition (PECVD) at a growth temperature of 250 °C.

[0057] 3) The epitaxial wafer obtained in step 2) is photolithographically exposed to reveal the ohmic contact cathode and ohmic contact anode fabrication regions. The silicon nitride passivation layer in these two regions is then completely removed by chemical etching. The etching solution used is a buffered oxide etchant with a HF to NH4F mass ratio of 1:7. The etching time is 100 s. Finally, inductively coupled plasma etching (ICP) is used to remove part of the AlGaN barrier layer in these two regions, with an etching depth of 4 nm. m, ICP etching process parameters: ICP power source upper electrode is 80W, lower electrode is 15W, BCl3 flow rate is 20sccm, Cl2 flow rate is 8sccm, chamber temperature is 20℃, etching time is 8s, followed by Ti / Al / Ni / Au metal evaporation, photoresist stripping and annealing. Annealing process parameters: annealing atmosphere is N2, annealing temperature is 850℃, holding time is 40s, heating rate is 15℃ / s, forming ohmic contact cathode and ohmic contact anode electrodes;

[0058] 4) The epitaxial wafer obtained in step 3) is photolithographically exposed to reveal the first Schottky contact anode fabrication region. The silicon nitride passivation layer in this region is then completely removed by chemical etching. The etching solution used for chemical etching is a buffered oxide etching solution with a mass ratio of HF to NH4F of 1:7. The chemical etching time is 100s. Then, part of the AlGaN barrier layer in this region is removed by inductively coupled plasma etching to a depth of 5nm. The process parameters for ICP etching are: 80W for the upper electrode and 15W for the lower electrode, 20sccm for the flow rate of BCl3, 8sccm for the flow rate of Cl2, 20℃ for the chamber temperature, and 10s for the etching time. Ni / Au metal evaporation and photoresist stripping are then performed to form the first Schottky contact anode.

[0059] 5) The epitaxial wafer obtained in step 4) is photolithographically exposed to reveal the second Schottky contact anode fabrication region. Then, the silicon nitride passivation layer and AlGaN barrier layer in this region are completely removed by chemical etching. The etching solution used for chemical etching is a buffered oxide etching solution with a mass ratio of HF to NH4F of 1:7. The chemical etching time is 100s. Then, part of the GaN channel layer in this region is removed by inductively coupled plasma etching with a etching depth of 2nm. The process parameters for ICP etching are: 150W for the upper electrode and 50W for the lower electrode, 20sccm for the flow rate of BCl3, 8sccm for the flow rate of Cl2, 20℃ for the chamber temperature, and 20s for the etching time. Then, Ni / Au metal evaporation and photoresist stripping are performed to form the second Schottky contact anode.

[0060] 6) The epitaxial wafer obtained in step 5) is photolithographically exposed to reveal the anode field plate preparation area. The silicon nitride passivation layer in this area is then completely removed by chemical etching. The etching solution used for chemical etching is a buffer oxide etching solution with a mass ratio of HF to NH4F of 1:7. The chemical etching time is 100s. Ni / Au metal evaporation and photoresist stripping are then performed to form the anode field plate, thus obtaining the hybrid anode Schottky diode.

[0061] Example 2:

[0062] A hybrid anode Schottky diode (structural schematic shown) Figure 2 As shown, it comprises a substrate 10, a GaN channel layer 20, an AlGaN barrier layer 30, a silicon nitride passivation layer 40, an ohmic contact cathode 50, an ohmic contact anode 60, a first Schottky contact anode 70, a second Schottky contact anode 80, and an anode field plate 90; the substrate 10, GaN channel layer 20, AlGaN barrier layer 30, and silicon nitride passivation layer 40 are sequentially stacked; the ohmic contact cathode 50 penetrates the silicon nitride passivation layer 40 and is partially embedded in the AlGaN barrier layer 30 to form an ohmic contact with the AlGaN barrier layer 30; the ohmic contact anode 60 penetrates the silicon nitride passivation layer 40 and is partially embedded in the AlGaN barrier layer 30 to form an ohmic contact with the AlGaN barrier layer 30. The AlGaN barrier layer 30 forms an ohmic contact; the first Schottky contact anode 70 penetrates the silicon nitride passivation layer 40 and is partially embedded in the AlGaN barrier layer 30 to form a Schottky contact; the second Schottky contact anode 80 penetrates the silicon nitride passivation layer 40 and the AlGaN barrier layer 30 and is partially embedded in the GaN channel layer 20 to form a Schottky contact; there is no direct contact between the ohmic contact anode 60, the first Schottky contact anode 70 and the second Schottky contact anode 80 (the gap is filled by silicon nitride); the anode field plate 90 penetrates the silicon nitride passivation layer 40 and is in contact with the AlGaN barrier layer 30.

[0063] The fabrication method of the above-mentioned hybrid anode Schottky diode is as follows:

[0064] 1) A GaN channel layer with a thickness of 3 μm was epitaxially grown on the surface of a Si substrate by metal-organic chemical vapor deposition (MOCVD) at a growth temperature of 850℃, and then an AlGaN barrier layer with a thickness of 17 nm was epitaxially grown at a growth temperature of 800℃.

[0065] 2) An 80 nm thick silicon nitride passivation layer was epitaxially grown on the surface of the AlGaN barrier layer by plasma-enhanced chemical vapor deposition (PECVD) at a growth temperature of 250 °C.

[0066] 3) The epitaxial wafer obtained in step 2) is photolithographically exposed to reveal the ohmic contact cathode and ohmic contact anode fabrication regions. The silicon nitride passivation layer in these two regions is then completely removed by chemical etching. The etching solution used is a buffered oxide etchant with a HF to NH4F mass ratio of 1:7. The etching time is 100 s. Finally, inductively coupled plasma etching (ICP) is used to remove a portion of the AlGaN barrier layer in these two regions, with an etching depth of 8 nm. The process parameters for ICP etching are as follows: the upper electrode of the ICP power source is 80W, the lower electrode is 15W, the flow rate of BCl3 is 20sccm, the flow rate of Cl2 is 8sccm, the chamber temperature is 20℃, and the etching time is 11s. Then, Ti / Al / Ni / Au metal evaporation, photoresist stripping, and annealing are performed. The annealing process parameters are as follows: the annealing atmosphere is N2, the annealing temperature is 870℃, the holding time is 30s, and the heating rate is 15℃ / s to form ohmic contact cathode and ohmic contact anode electrodes.

[0067] 4) The epitaxial wafer obtained in step 3) is photolithographically exposed to reveal the first Schottky contact anode fabrication region. The silicon nitride passivation layer in this region is then completely removed by chemical etching. The etching solution used for chemical etching is a buffered oxide etching solution with a mass ratio of HF to NH4F of 1:7. The chemical etching time is 100s. Then, part of the AlGaN barrier layer in this region is removed by inductively coupled plasma etching to a depth of 10nm. The process parameters for ICP etching are: 80W for the upper electrode and 15W for the lower electrode, 20sccm for the flow rate of BCl3, 8sccm for the flow rate of Cl2, 20℃ for the chamber temperature, and 13s for the etching time. Ni / Au metal evaporation and photoresist stripping are then performed to form the first Schottky contact anode.

[0068] 5) The epitaxial wafer obtained in step 4) is photolithographically exposed to reveal the second Schottky contact anode fabrication region. Then, the silicon nitride passivation layer and AlGaN barrier layer in this region are completely removed by chemical etching. The etching solution used for chemical etching is a buffered oxide etching solution with a mass ratio of HF to NH4F of 1:7. The chemical etching time is 100s. Then, part of the GaN channel layer in this region is removed by inductively coupled plasma etching with a etching depth of 5nm. The process parameters for ICP etching are: 150W for the upper electrode and 50W for the lower electrode, 20sccm for the flow rate of BCl3, 8sccm for the flow rate of Cl2, 20℃ for the chamber temperature, and 26s for the etching time. Then, Ni / Au metal evaporation and photoresist stripping are performed to form the second Schottky contact anode.

[0069] 6) The epitaxial wafer obtained in step 5) is photolithographically exposed to reveal the anode field plate preparation area. The silicon nitride passivation layer in this area is then completely removed by chemical etching. The etching solution used for chemical etching is a buffer oxide etching solution with a mass ratio of HF to NH4F of 1:7. The chemical etching time is 100s. Ni / Au metal evaporation and photoresist stripping are then performed to form the anode field plate, thus obtaining the hybrid anode Schottky diode.

[0070] Comparative example:

[0071] A Schottky diode (structural schematic diagram shown) Figure 3 As shown), except that the first Schottky contact anode 70 and the second Schottky contact anode 80 are replaced with ohmic contact anode 60, the thickness of the replacement portion is the same as that of ohmic contact anode 60, and the rest is exactly the same as the hybrid anode Schottky diode of Example 1.

[0072] Performance testing:

[0073] The reverse leakage current and breakdown performance comparison diagram of the hybrid anode Schottky diode of Example 1 and the comparative Schottky diode is shown in Figure 1. Figure 4 As shown.

[0074] Depend on Figure 4 It can be seen that: compared with the Schottky diode of the comparative example, the reverse current of the hybrid anode Schottky diode of Example 1 is reduced by one order of magnitude, and the reverse breakdown voltage is increased by about 41.5%, indicating that the electrical characteristics of the hybrid anode Schottky diode of Example 1 under reverse bias are significantly improved.

[0075] Furthermore, the same tests revealed that the hybrid anode Schottky diode of Example 2 exhibited significantly improved electrical characteristics under reverse bias compared to Schottky diodes with the same anode length and anode-cathode spacing (i.e., a comparative example was set up for Example 2 as in Example 1 and the comparative example).

[0076] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A hybrid anode Schottky diode, characterized in that, The composition includes a substrate, a GaN channel layer, an AlGaN barrier layer, and a silicon nitride passivation layer stacked sequentially, and also includes an ohmic contact cathode, an ohmic contact anode, a first Schottky contact anode, a second Schottky contact anode, and an anode field plate; the ohmic contact cathode penetrates the silicon nitride passivation layer and is partially embedded in the AlGaN barrier layer to form an ohmic contact with the AlGaN barrier layer; The ohmic contact anode penetrates the silicon nitride passivation layer and is partially embedded in the AlGaN barrier layer to form an ohmic contact with the AlGaN barrier layer. The first Schottky contact anode penetrates the silicon nitride passivation layer and is partially embedded in the AlGaN barrier layer to form a Schottky contact with the AlGaN barrier layer; The second Schottky contact anode penetrates the silicon nitride passivation layer and the AlGaN barrier layer, and is partially embedded in the GaN channel layer to form a Schottky contact with the GaN channel layer; The anode field plate penetrates the silicon nitride passivation layer and is in contact with the AlGaN barrier layer.

2. The hybrid anode Schottky diode according to claim 1, characterized in that: The substrate is one of SiC substrate, Si substrate, sapphire substrate, and GaN single crystal substrate.

3. The hybrid anode Schottky diode according to claim 1, characterized in that: The thickness of the GaN channel layer is 1 μm to 5 μm; the thickness of the AlGaN barrier layer is 5 nm to 17 nm; and the thickness of the silicon nitride passivation layer is 50 nm to 100 nm.

4. The hybrid anode Schottky diode according to any one of claims 1 to 3, characterized in that: The ohmic contact cathode is composed of at least one of Ti, Al, Ni, and Au; the ohmic contact anode is composed of at least one of Ti, Al, Ni, and Au.

5. The hybrid anode Schottky diode according to any one of claims 1 to 3, characterized in that: The first Schottky contact anode is composed of at least one of Ni, W, Pt, Ti, and Au; the second Schottky contact anode is composed of at least one of Ni, W, Pt, Ti, and Au; and the anode field plate is composed of at least one of Ni, W, Pt, Ti, and Au.

6. A method for fabricating a hybrid anode Schottky diode as described in any one of claims 1 to 5, characterized in that, Includes the following steps: 1) GaN channel layer and AlGaN barrier layer are epitaxially grown sequentially on the substrate surface by metal-organic chemical vapor deposition or molecular beam epitaxy; 2) A silicon nitride passivation layer is epitaxially grown on the surface of the AlGaN barrier layer by low-pressure chemical vapor deposition, plasma-enhanced chemical vapor deposition, or atomic layer deposition. 3) The epitaxial wafer obtained in step 2) is exposed by photolithography to expose the ohmic contact cathode preparation area and the ohmic contact anode preparation area. The silicon nitride passivation layer in these two areas is completely removed by chemical etching. Then, part of the AlGaN barrier layer in these two areas is removed by inductively coupled plasma etching. Finally, metal evaporation, photoresist stripping and annealing are performed to form the ohmic contact cathode and ohmic contact anode electrodes. 4) The first Schottky contact anode fabrication region is exposed by photolithography on the epitaxial wafer obtained in step 3). The silicon nitride passivation layer in this region is completely removed by chemical etching. Then, part of the AlGaN barrier layer in this region is removed by inductively coupled plasma etching. Finally, metal evaporation and photoresist stripping are performed to form the first Schottky contact anode. 5) The epitaxial wafer obtained in step 4) is photolithographically exposed to expose the second Schottky contact anode fabrication region. Then, the silicon nitride passivation layer and AlGaN barrier layer in this region are completely removed by chemical etching. Then, part of the GaN channel layer in this region is removed by inductively coupled plasma etching. Then, metal evaporation and photoresist stripping are performed to form the second Schottky contact anode. 6) The epitaxial wafer obtained in step 5) is photolithographically exposed to expose the anode field plate preparation area. Then, the silicon nitride passivation layer in this area is completely removed by chemical etching. Then, metal evaporation and photoresist stripping are performed to form the anode field plate, thus obtaining the hybrid anode Schottky diode.

7. The preparation method according to claim 6, characterized in that: Step 1) Grow a GaN channel layer by metal-organic chemical vapor deposition at a growth temperature of 850℃~950℃; Step 2) Grow an AlGaN barrier layer by metal-organic chemical vapor deposition at a growth temperature of 750℃~850℃; Step 3) Grow a silicon nitride passivation layer by plasma-enhanced chemical vapor deposition at a growth temperature of 230℃~320℃.

8. The preparation method according to claim 6 or 7, characterized in that: The etching solution used in steps 3) to 6) is a buffered oxide etching solution, and the etching time is 50s to 100s; the annealing in step 3) is carried out in a nitrogen atmosphere at a temperature of 800℃ to 900℃, and the annealing time is 20s to 60s.

9. The preparation method according to claim 6 or 7, characterized in that: Step 3) The etching depth of the AlGaN barrier layer is 2nm to 8nm; Step 4) The etching depth of the AlGaN barrier layer is 3nm to 13nm; Step 5) The etching depth of the GaN channel layer is 2nm to 5nm.

10. An electronic product, characterized in that, The invention comprises a hybrid anode Schottky diode as described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Transverse Schottky diode based on P-GaN cap layer and interdigital structure, and preparation method of transverse Schottky diode

    CN111477690A

  • Schottky barrier diode and preparation method and application thereof

    CN115939223A